Implementation of a pavement management system for maintenance and rehabilitation of airport surfaces. (December 2019) - Di Mascio, Paola; Moretti, Laura
Abstract: Airport pavements should satisfy safe and regular aircraft operations; thus, it is necessary to monitor these surfaces and implement expensive maintenance and rehabilitation works. The Airport Pavement Management System (APMS) is an approach to monitor the pavement condition and to determine the priorities for intervention, to plan, and to allocate resources through procedures. The method for monitoring pavement conditions is currently adopted by the airport management company because it is necessary to the airport operability. The study focuses on the paved network of an Italian airport that is composed of a runway, a parallel taxiway and five exit taxiways. Measures of load bearing capacity, transversal and longitudinal evenness, pavement-tire adherence, and pavement distresses were collected and merged to identify the needed maintenance and rehabilitation works. The results revealed the presence of critical sections, where several structural and functional distresses were. The needed structural and functional works involved the greater parts of the runway and the parallel taxiway, and two exit taxiways. Given the high operational impact of the needed works, they were scheduled to be conducted within three phases in order to minimize the impact on the traffic, reducing the closure period to 15 consecutive days. In general, the results summarized approaches typical of different conditions: the article has highlighted that the Pavement Management System (PMS) requires multiple analyses to consider various indices and correctly manage existing pavements having different competences to conduct comprehensive and appropriate analyses.